The casuistical tradition in Shakespeare, Donne, Herbert, and Milton - Slights, Camille Wells (Princeton Legacy Library, 2017)
To show how the casuistical tradition illuminates the study of major literary works in the English Renaissance, Camille Slights traces the emergence of casuistry in the sixteenth and seventeenth centuries and discusses its influence on the moral imaginations of Shakespeare, Donne, Herbert, and Milton. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.